Er luthersk politisk teologi valgbeslægtet med liberalisme og republikanisme? - Assel, Heinrich (Dansk Teologisk Tidsskrift, 2011)
Svend Andersen’s book Macht aus Liebe (Love in Power) is a vital contribution to the discussion about the affiliation of various political theologies to liberalism. The book contains of substantial, refreshingly provocative reconstruction of the political ethics in Luther and Danish Luthernism in the spirit of political liberalism from Kant to Rawls and Habermas’ republicanism; and is a genuine Danish contribution to an European comparative analyses of political confessional cultures.